Answered

At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

[tex]\sf Solve\: this \: with\; steps:-[/tex]
[tex]\bf 4-7x=1-6x[/tex]


Sagot :

Answer:

x = 3

Explanation:

4 - 7(x) = 1 - 6(x)

-7(x) + 6(x) = 1 - 4

-(x) = -3

x = 3

Check:

  • 4 -7(3) = 1-6(3)
  • 4 - 21 = 1 - 18
  • -17 = -17

Hence, x = 3 confirmed as L.H.S = R.H.S

[tex]\qquad\qquad\huge\underline{{\sf Answer}}[/tex]

Here we go ~

[tex]\qquad \sf  \dashrightarrow \:4 - 7x = 1 - 6x[/tex]

[tex]\qquad \sf  \dashrightarrow \:4 - 1 = 7x- 6x[/tex]

[tex]\qquad \sf  \dashrightarrow \:x = 3[/tex]

so, we got the value of x as 3